2017
DOI: 10.1097/iyc.0000000000000104
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Competencies in U.S. Early Intervention/Early Childhood Special Education Service Systems

Abstract: In 2015, the Division for Early Childhood of the Council for Exceptional Children released a position statement on leadership in early intervention and early childhood special education (EI/ECSE). Division for Early Childhood emphasized the importance of developing and supporting high-quality leadership within and across all levels of EI/ECSE service systems. Moreover, there was a call for related research because of the paucity of related research in the field. This cross-sectional survey was designed to addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…The journey of leading change in early childhood settings has been further presented in a model with two dimensions: (1) leaders’ behaviours and attitudes – being cooperative, supportive, culturally sensitive and reflective, as well as valuing staff – and (2) leaders’ tasks – situational analysis, self-identification of leadership and management roles, and the endeavours for planning and implementing change through stages (Davis, 2012). A national survey conducted in the USA has demonstrated five competency areas that are considered important for successful early childhood leadership, including professional learning, effective relationships, shared responsibility, data use and effective communication (Bruns et al, 2017). Chan (2018) also found that systems thinking, reflective thinking, flexible thinking, network-building, continuous professional development and the development of contextual intelligence are important components in successful early childhood leadership in Hong Kong kindergartens.…”
Section: Leadership Matters In Early Childhoodmentioning
confidence: 99%
“…The journey of leading change in early childhood settings has been further presented in a model with two dimensions: (1) leaders’ behaviours and attitudes – being cooperative, supportive, culturally sensitive and reflective, as well as valuing staff – and (2) leaders’ tasks – situational analysis, self-identification of leadership and management roles, and the endeavours for planning and implementing change through stages (Davis, 2012). A national survey conducted in the USA has demonstrated five competency areas that are considered important for successful early childhood leadership, including professional learning, effective relationships, shared responsibility, data use and effective communication (Bruns et al, 2017). Chan (2018) also found that systems thinking, reflective thinking, flexible thinking, network-building, continuous professional development and the development of contextual intelligence are important components in successful early childhood leadership in Hong Kong kindergartens.…”
Section: Leadership Matters In Early Childhoodmentioning
confidence: 99%
“…Competence and knowledge are important features for teachers' transformation into leaders in special education [16]. Moreover, there is consensus in the literature in the stressed the need for creating partnership between university preparation programs, professional organizations, educational researchers, educational institutions, and local communities to ensure the development of essential leadership skills in school principals, teachers and administrators [17].…”
Section: Discussionmentioning
confidence: 99%
“…In [16] conducted to define early intervention/ early childhood educational service systems as required by the Education for Individuals with Special Needs Act. The results of the study showed the necessity of having competence and knowledge aspects among teachers, who intend to become leaders in the field of special education.…”
Section: Introductionmentioning
confidence: 99%
“…Research studies on leadership in ECE in the United States tend to be descriptive (Abel et al, 2017;Fleming & Love, 2003;Jacobson & Cypres, 2012;Kagan & Hallmark, 2001;LaRocc., Sopko, Bruns, & Gupta, 2014;Mujis et al, 2004;Muñoz, Boulton, Johnson, & Unal, 2015). Few studies employed quantitative non-experimental cross-sectional surveys (Bruns et al, 2017;Myers & Palmer, 2015). To examine how childcare centre directors made their centres visible and successful, Myers and Palmer (2015) collected data at 200 university campus-based childcare centres across the country.…”
Section: The United States -View From Hierarchy Towards Educational Lmentioning
confidence: 99%